PERSEPSI DAN SIKAP PETANI TERHADAP PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN USAHATANI SAWI (Brassica Juncea L) DI DESA NETPALA, KECAMATAN MOLLO UTARA, KABUPATEN TIMOR TENGAH SELATAN - Antunia Finit; Tomycho Olviana; Serman Nikolaus (Undana Press, 2021)
This research on Farmer's Perceptions and Attitudes Toward the Role of Agricultural Extension in Mustard Farming Development was conducted in the village of Netpala, Mollon District, North Central Timor Regency in August 2019. This study aims to determine: the role of extension personnel; farmers 'perceptions ,farmers' attitudes. The method used in this research is a survey method. The research location was determined deliberately, the respondents were assigned as many as 52 people who were randomly selected. The types of data collected were primary data and secondary data. To determine the first objective, the data were analyzed descriptively quantitatively and to determine the second and third objectives, the data were analyzed descriptively by using a Likert scale. The research result shows that; the role of extension workers in the development of mustard farming, according to the assessment of farmers, most farmers have felt the impact of extension activities. The perception of farmers on the role of agricultural extension agents in the development of mustard farming in Netpala Village, Mollo Utara District, South Central Timor Regency has a fairly good perception. with an average score of 53,84. the attitude of farmers towards the role of agricultural instructors in the development of mustard (Brassica Juncea L) farming in Netpala Village, Mollo Utara District, Timor Tengah Selatan Regency, has an agreeable attitude with an average score of 88,46. Therefore, it can be concluded that the mustard farmers in Netpala Village have a fairly good perception and agree with the role of agricultural extension agents in the development of mustard farming.